Family support in preventing relapse in individuals with mental disorders in a Malawei public health center, Indonesia - Hardiyanti, Rina; Herman, Herman (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Relapse rates remain high among people with mental disorders. The family plays a crucial role in helping people with mental disorders prevent relapse. However, providing support often has challenges due to the family's lack of knowledge in dealing with schizophrenia patients. Purpose: To provide an overview of family support in the prevention of relapse in patients with mental disorders at the public health center in Malawi. Methods: This study used a quantitative method with a descriptive research design. A total sample of 39 families of people with mental disorders who had no history of relapse was the population of the study. Results: The results of this study showed that the majority of family members provide adequate family support (92.3%) and 7.7% provide poor support to individuals with mental disorders. The average age of respondents was 42 years; the majority were women (56.4%), Maluku ethnicity (28.3%), and extended family type (66.7%). Conclusion: The majority of family support for individuals with mental disorders is well supported to prevent relapse. The government needs to pay attention to the families of patients with mental disorders to prevent relapse.